A latitudinal gradient of microbial β‐diversity in continental paddy soils. Issue 4 (15th February 2021) - Xiao, Xian; Zhang, Na; Ni, Haowei; Yang, Yunfeng; Zhou, Jizhong; Sun, Bo; Liang, Yuting
Abstract: Aim: The β‐diversity of plants and animals generally decreases with increasing latitudes. Here, we tested whether this relationship also holds for soil microbes at both functional and taxonomic levels. Location: China. Time period: Between June and October 2013. Major taxa studied: Soil archaea, bacteria, and functional genes. Methods: We used a spatially explicit 'L‐shaped' sampling strategy in 39 paddy fields in China to study the pattern of soil microbial β‐diversity (i.e., species turnover, β z ) across a latitudinal gradient (19.75° N to 47.58° N), with 11 soil samples taken within a 100 m × 100 m plot from each field. Archaeal and bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using Illumina MiSeq; microbial functional genes involved in C/N/P/S cycling were detected by GeoChip. Results: We showed that the microbial β‐diversity varied considerably across taxonomic and functional groups. For both soil microbial communities and functional genes, β‐diversity decreased significantly along elevated latitudes at the continental scale. Woesearchaeota of archaeal communities, Bacteroidetes of bacterial communities, and the functional genes involved in methane production displayed the greatest decreases. Both mean temperature during the growing season of rice plants and paddy soil heterogeneity contributed to the latitudinal patterns. Further analyses indicated that temperature was more important than soil heterogeneity in driving the β‐diversity of microbial communities and functional genes. Main conclusions: These results highlight the importance of temperature‐driven soil microbial β‐diversity and suggest the potential to predict the changes of microbial diversity with climate change.